(untitled) (Revista de Ciências Agroveterinárias, 2025)
The article examines the development of rural areas under conditions of decentralization. The primary objectives of sustainable development of rural areas include the establishment of a stable social environment. A rural area, as an agrosocial system, is an objective combination of three key components - environmental, economic, and social - which together ensure the resilience of this system. In Ukraine, there are certain prerequisites for sustainable development. However, there is a lack of clear principles and regulatory methods at the level of rural settlements that would take into account the essential characteristics of rural development. Measures for sustainable development of rural areas are currently being formed as a distinct direction of state policy. The state’s influence on rural areas is exercised through the management and regulatory functions of public policy, which are reflected in legislative and regulatory acts. The article addresses the socio-economic aspects of developing local self-governance in rural areas, the particularities of organizing life in rural territories, and the formation of potential for growth. It justifies the need to enhance activities aimed at increasing the role of local self-governance and implementing modern principles of economic reform in rural areas. The article confirms that the decentralization process is complex, involving numerous contradictions related to finding the optimal model of local self-governance. The risks and threats associated with the decentralization process are identified, and the potential impact on the socio-economic development of rural areas is substantiated. The article emphasizes the necessity of creating a comprehensive vision of relevant measures, establishing clear criteria for their assessment, and forecasting their influence on the socio-economic development of rural areas to enhance the effectiveness of decentralization policies. It is demonstrated that the development of a mechanism for diversifying rural area growth must consider strategic directions and an analysis of the current state of socio-ecological-economic development of rural territories.